Implementasi Kompres Aloevera terhadap Penurunan Suhu Tubuh pada Anak dengan Kejang Demam Sederhana - Malik, Asef Abdul; Triana, Noor Yunida (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Child health encompasses physical, mental, and social well-being, which must be maintained optimally by parents and the community through comprehensive child protection efforts. Toddlers are particularly vulnerable to various illnesses such as fever, acute respiratory infections, and diarrhea, all of which can trigger febrile seizures. Prompt and appropriate management of hyperthermia is essential to prevent serious complications, including seizures and death. One non-pharmacological method that can be used to reduce body temperature is an Aloe vera compress. This case study aims to analyze the effectiveness of Aloe vera compresses in lowering body temperature in children experiencing febrile seizures. The study employed a descriptive case study approach with data collected through physical examination, interviews, and direct observation of the patient. The results showed a decrease in body temperature from 39℃ to 36.5℃ after the administration of Aloe vera compresses over three days (3×24 hours), accompanied by clinical improvement such as the absence of shivering and increased patient comfort. Based on these findings, it is recommended that healthcare providers consider Aloe vera compresses as an non-pharmacological therapy in managing hyperthermia in children, that parents be educated on proper application techniques, and that further research using an experimental design be conducted to evaluate the effectiveness of this intervention in a larger population.